Muslim-Christian polemic during the Crusades : the letter from the people of Cyprus and Ibn Abī Ṭālib al-Dimashqī's response - Ebied, R. Y. (History of Christian-Muslim relations, 2005)
"This volume comprises an edition and English translation of the response in Arabic made by the fourteenth century scholar Ibn Abi Talib al-Dimashqi to a letter sent to him by anonymous Christians from Cyprus. The Christian letter was also sent to al-Dimashqi's contemporary Ibn Taymiyya, and this response is thus a parallel to Ibn Taymiyya's al-Jawab al-sahih."